Differentiation of Human Embryonic Stem Cells to Sympathetic Neurons: A Potential Model for Understanding Neuroblastoma Pathogenesis. (1st November 2018) - Carr-Wilkinson, Jane; Prathalingam, Nilendran; Pal, Deepali; Moad, Mohammad; Lee, Natalie; Sundaresh, Aishwarya; Forgham, Helen; James, Peter; Herbert, Mary; Lako, Majlinda; Tweddle, Deborah A.
Abstract : Background and Aims . Previous studies modelling human neural crest differentiation from stem cells have resulted in a low yield of sympathetic neurons. Our aim was to optimise a method for the differentiation of human embryonic stem cells (hESCs) to sympathetic neuron-like cells (SN) to model normal human SNS development. Results . Using stromal-derived inducing activity (SDIA) of PA6 cells plus BMP4 and B27 supplements, the H9 hESC line was differentiated to neural crest stem-like cells and SN-like cells. After 7 days of PA6 cell coculture, mRNA expression of SNAIL and SOX-9 neural crest specifier genes and the neural marker peripherin ( PRPH ) increased. Expression of the pluripotency marker OCT 4 decreased, whereas TP53 and LIN28B expression remained high at levels similar to SHSY5Y and IMR32 neuroblastoma cell lines. A 5-fold increase in the expression of the catecholaminergic marker tyrosine hydroxylase (TH ) and the noradrenergic marker dopamine betahydroxylase (DBH ) was observed by day 7 of differentiation. Fluorescence-activated cell sorting for the neural crest marker p75, enriched for cells expressing p75, DBH, TH, and PRPH, was more specific than p75 neural crest stem cell (NCSC) microbeads. On day 28 post p75 sorting, dual immunofluorescence identified sympathetic neurons by PRPH and TH copositivity cells in 20% of the cell population. Noradrenergic sympathetic neurons, identified by copositivity for both PHOX2B and DBH, were present in 9.4% ± 5.5% of cells. Conclusions . We have optimised a method for noradrenergic SNS development using the H9 hESC line to improve our understanding of normal human SNS development and, in a future work, the pathogenesis of neuroblastoma.